EKSPERIMENTASI STRATEGI PEMBELAJARAN SYSTEMATIC PROBLEM SOLVING TERHADAP HASIL BELAJAR SISWA - Sulaiman, Sulaiman (JURNAL e-DuMath, 2017)
This study aims to determine the difference in average math student learning outcomes obtained using systematic problem solving learning strategies with average math student learning outcomes obtained using expository teaching strategy. The population in this study is the first semester of class X Â SMK Islam Adiluwih 2015-2016 school year, amounting to 137 people and is divided into five classes. The results of the data analysis test two parties at significant level 5% results obtained thitung = 3.66 and ttable = 1.99, which means there are differences in the average math student learning outcomes obtained using systematic learning strategy problem expository solving strategies. Then the t-test data analysis of the parties with a significant level of 5% obtained thitung = 3.66 and ttable = 1.67, which means the average student learning outcomes obtained using systematic problem solving learning strategy is better than expository teaching strategy.